Use and safety of long-acting β2-agonists for pediatric asthma. Issue 3 (June 2010) - Elkout, Hajer; McLay, James S; Simpson, Colin R; Helms, Peter J
Asthma guidelines recommend the use of long-acting β2 -agonists (LABAs) as the preferred add-on therapy for adults and children over 5 years of age when asthma is inadequately controlled by inhaled corticosteroids alone. It has been suggested that LABA use may be associated with an increased risk of morbidity and mortality; however, this view is controversial since study findings have been inconsistent. While the safety profile of LABA monotherapy has been questioned, the value of concomitant inhaled corticosteroids to eliminate possible risks remains unproven. There is a paucity of efficacy and safety data for LABA use in children, and existing evidence is not sufficiently convincing to demonstrate a clear position for LABAs in the management of childhood asthma. The main aims of this article are to place LABAs in context in the management of childhood asthma and evaluate the current evidence for safety and efficacy.